2015
DOI: 10.5539/ass.v11n23p73
|View full text |Cite
|
Sign up to set email alerts
|

The Application of a Combined Delphi-AHP Method in Maritime Transport Research-A Review

Abstract: Although the Delphi and AHP techniques have been extensively utilised in maritime transport research, the application of a combination of both techniques together in this sector is still limited. Hence, this paper aims to review the application of a combined Delphi and AHP method in maritime transport research through a literature review process. Among others, this study looks into the area of research, the number of expert respondents employed, the minimum prerequisite set for the selection of respondents and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
(78 reference statements)
0
17
0
Order By: Relevance
“…As MCDM techniques are based on expert judgment, and number of qualified experts is usually limited to 5 and 25 (Armacost et al, 1994[ 4 ]; Peterson et al, 1994[ 43 ]; Mawapanga and Debertin, 1996[ 33 ]; Al-Harbi, 2001[ 3 ]; Landeta, 2006[ 30 ]; Arof, 2015[ 5 ]; Kil et al, 2016[ 26 ]). In other words, the advantage of these methods is that they do not require a large sample size, and 10 to 15 qualified experts are adequate to prioritize and solve complex problems.…”
Section: Methodsmentioning
confidence: 99%
“…As MCDM techniques are based on expert judgment, and number of qualified experts is usually limited to 5 and 25 (Armacost et al, 1994[ 4 ]; Peterson et al, 1994[ 43 ]; Mawapanga and Debertin, 1996[ 33 ]; Al-Harbi, 2001[ 3 ]; Landeta, 2006[ 30 ]; Arof, 2015[ 5 ]; Kil et al, 2016[ 26 ]). In other words, the advantage of these methods is that they do not require a large sample size, and 10 to 15 qualified experts are adequate to prioritize and solve complex problems.…”
Section: Methodsmentioning
confidence: 99%
“…The Delphi method is considered one of the most well-known methodologies that allow a consensus to be reached in a decision-making problem (Sekhar et al, 2015). The use of the method originated in the 1950s, when it was first used in a number of surveys conducted by RAND Corporation to develop a technique that would make it possible to gain the most reliable consensus from a group of people with specific expertise (Dalkey & Helmer, 1963;Okoli & Pawlowski, 2004;Arof, 2015). It is the most effective method in terms of collecting experts' opinions about problems, in which there are no clear criteria for evaluation (Taleai & Mansourian, 2008), and it lies between qualitative and quantitative research techniques (Steward, 2001).…”
Section: The Delphi Techniquementioning
confidence: 99%
“…The first round usually involves brainstorming and seeks to obtain an open response about the topic. The panelists are asked to complete an open-ended questionnaire, describe their particular point of view and identify key factors that affect the decision-making process of the problem (Arof, 2015). The subsequent rounds are much more specific to the situation and the research question, and seek to quantify the identified factors from the first round.…”
Section: The Delphi Techniquementioning
confidence: 99%
“…Regarding the marginal number of feedback in the second round, we terminated the further rounds of the survey. The numbers of round have been reported to be varied but found average at two to three rounds [126]. Many studies stopped at the secondround [122,127].…”
Section: Experts Panelmentioning
confidence: 99%